Histomorphological and Biochemical Analyses Following Adminstration of Methanol Leaf Extract of Nicotiana tabacum (Tobacco) on the Cerebellum of Wistar Rats (Journal of Experimental and Clinical Anatomy, 2024)
BACKGROUND: The cerebellum, an essential brain region, coordinates voluntary movements, balance, and posture. While both beneficial and toxic effects of tobacco on various bodily systems have been reported, there's limited data on its neurotoxic effect on the cerebellum and motor functions.AIM: This study aimed to histomorphologically and biochemically assess the effects of methanol leaf extract of Nicotiana tabacum (MLNT) on the brain and cerebellum of Wistar rats.METHODOLOGY: Twenty male Wistar rats were divided into four groups (A-D) of five animals each, with A as control (Tween 80/Oil; 1:4) and B-D receiving MLNT at 200, 400, and 600 mg/kg, respectively, for four weeks with concurrent measurement of body weight.RESULTS: Significant percentage weight changes were observed in all treatment groups compared to controls. Histological analysis revealed neurodegeneration in the cerebellar histoarchitecture of MLNT-treated groups compared with controls. Although no significant difference was observed in glutathione (GSH) levels, a significant increase in Malondialdehyde (MDA) level was observed at 200 mg/kg MLNT dosage compared to control (P<0.05).CONCLUSION: This study indicates that methanolic leaf extract of Nicotiana tabacum induces neurotoxicity in Wistar rat cerebellum, potentially via heightened oxidative stress, particularly at 200 mg/kg dosage.